ELIMINATION OF DUPLICATE PACKETS FROM THE NETWORK USING REDUNDANCY AWARE HIERARCHICAL TREE ALTERNATIVE PATH ALGORITHM - Thayyil, Chinnu.J.; Glory, P.J.Gladys (IJRDO -Journal of Computer Science Engineering, 2016)
The wireless sensor network (WSN) is a grouping of sensing, computation, and communication into a particular tiny device. A sensor network consists of an array of many sensor networks of various types unified by a wireless communication network. This paper has largely described the feature and the substance of congestion control in WSN and survey the study related to the Congestion Control Protocols and Algorithms for WSNs. In this paper we applied Redundancy Aware Hierarchical Tree Alternative Path (RAHTAP) algorithm, this algorithm eliminates the duplicate packets from the network and attain reduction in network load as per packets basis which generate lively substitute path from source to sink.